The karst springs of the Kanin massif - Komac, Blaž (Geografski zbornik, 2001)
In this article the author summarizes the geographical, hydrological, and geological studies of the Kanin massif done to date and on the basis of physical and chemical analyses of the water describes the basic geographical characteristics of the karst springs below the mountains. Using recession curve analysis, the extent of the Glijun spring catchment area has been determined. Catchment areas, draining, and the location of a karst watershed depend on the quantity of water in the aquifer. Due to the overlapping of the catchment areas of various springs, the dumping of dangerous wasted in the high mountains can cause the pollution of many springs. Because the aquifers in the limestone and dolomite Kanin massif are closely linked to those in the Quaternary of the Bovec Basin, protecting the high mountain karst also protects the sources of potable water in the valley.
Keywords: Julian Alps; Julijske Alpe; Kanin; kraške vode; kraški izviri; podzemne vode